(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Climate change has become a pressing concern for Nigeria in its efforts to ensure food and nutritional security for a rapidly growing population. In light of the challenges faced, it is essential to quantify the optimal weather conditions necessary for achieving higher yields. The aim of implementing adaptation is to effectively address potential climate risks in the forthcoming decades as the climate continues to evolve. This research aid in guiding choices made by farmers and policymakers, with consequences for a spectrum of timelines ranging from immediate tactical approaches to extensive long-term strategies. The adaptation index was developed following six (6) steps. Indicators selected for the index comprises of; Methods of fishery, Altered fishing periods, Varieties of Fishing gears, Crafts Management, Depth, Fishing frequency, Post-harvest techniques, and Varieties of baits. KMO and Bartlett’s test was conducted using principal component analysis (PCA) to thoroughly evaluate the validity of the chosen indicators and sub-indicators. The obtained (KMO) value was 0.541, and it was acceptable. The approximate Chi-Square value was 412.836, with a significance value (p) of 0.000, which is less than 0.001. This finding indicates that the correlation matrix is not an identity matrix, reflecting a strong relationship among the variables. The reliability coefficient was measured at 0.89, which exceeds the standard value of 0.70. The adaptation index measures the climate-resilient practices embraced by fishermen. By quantifying their level of adaptation to climate change, this index provides valuable insights into the effectiveness of existing fishing practices in mitigating climate-related risks.